STUDI PSIKOLINGUISTIK: GANGGUAN SIGMATISMUS PADA PENGUCAPAN FONEM /S/ INDIVIDU DEWASA - Annisa Putri Ramadhini; Keti Wahdania; Sundawati Tisnasari (Jurnal Bastra (Bahasa dan Sastra), 2026)
This study examines sigmatism, a speech disorder characterized by difficulties in pronouncing the phoneme /s/. A 20-year-old individual who has been experiencing sigmatism since the age of 5 serves as the case study. Employing a descriptive qualitative approach, data collection involves observation, recording, and note-taking during interviews. The research focuses on identifying the multifaceted factors contributing to sigmatism and the resultant phonetic variations. The findings indicate that a short tongue is a contributing factor to the sigmatism disorder in this case, leading to the production of /ch/ and /th/ sounds instead of /s/.